Social Education Seminar for PKH Beneficiary Families in Nisam Subdistrict, North Aceh : (Theme: The Role of PKH Beneficiary Mothers in Family and Social Life) - Nurbaiti, Nurbaiti; Lhokweng, Amiruddin (Institute of Education and Social Research, 2023)
This article discusses the role of mothers as Beneficiary Families (KPM) in the Family Hope Program (PKH) in the family and social life in Nisam Subdistrict, North Aceh. This program aims to improve the welfare of poor families through financial assistance provided to the KPM mothers. The analysis results show that the role of KPM PKH mothers is significant in supporting family life and contributing to social changes in the local community, maintaining a positive attitude in interacting with others. This conclusion illustrates that the activities of delivering lectures in the PKH program have a broad impact in improving the understanding, skills, and active participation of KPM PKH mothers, and have the potential to bring about positive changes at the social and economic levels for the benefiting community.